Implementation of Drug Administration with High Awareness (LASA/ Look Alike Sound Alike and High Alert) for Patient Safety at Pharmacies in Surakarta - Handri Mursiti; Galau Menanti Embri Baskara Putra Mesias; Peni Indrayudha (Universitas Muhammadiyah Surakarta, 2022)
LASA (Look Alike Sound Alike) are drugs that have similar names, looks and speech and need to be watched out for to prevent no errors in taking medication (dispensing error) by pharmacists. High-alert (HA) medication is a drug that must be watched out for because it often causes errors or serious errors (sentinel events) and drugs that have a high risk of causing Adverse Drug Reactions (ADR). One of the pharmacist duties at a pharmacy is to organize LASA and HA drugs properly to prevent medication errors. The purpose of this study is to determine the knowledge of pharmacist in the city of Surakarta on the process of good and safe drug storage and able to implement safe and high alert drug storage for patient/consumer safety. The type of research is experimental research. The study was conducted from September 1, 2021 to January 20, 2022. The number of samples were 117 pharmacists who worked in different pharmacy locations. The data obtained were scored and analyzed using the SPPS 25 test, the Shapiro-Wilk normality test, followed by the Paired sample T-Test. The results of this study indicate that there is an effect of socialization intervention using the HA and LASA flyer, namely an increase in knowledge and implementation of the arrangement of HA and LASA drugs. Data showed that the results of pre-test 17.52% and post-test 89.74% (p=0.000; p0.05). From this study, it was found that there was a significant change in the level of implementation of the LASA and HA drug arrangement from pharmacists after the intervention using the LASA/HA drug arrangement flyer.